Pharmacological effects of berberine on models of ulcerative colitis: A meta-analysis and systematic review of animal studies - Hu, Shuangyuan; Wei, Pengfei; Li, Wei; Liu, Qingsong; Chen, Shuanglan; Hu, Caiyu; Guo, Xiaochuan; Ma, Xiao; Zeng, Jinhao; Zhang, Yi (Frontiers in Pharmacology, 2022)
Berberine (BBR) is the main active constituent of the Rhizoma coptidis (Huanglian) and has multiple biological activities. Although current evidence suggests that the BBR has a multi-target effect in ulcerative colitis (UC), its action and mechanism are unclear. The purpose of this meta-analysis was to assess the pharmacological effects and potential mechanisms of BBR in UC models. Studies were searched from four databases (PubMed, Embase, Web of Science, and Cochrane Library) until March 2022. Standardized mean difference (SMD) and 95% confidence intervals (CI) were used for the adjudication of outcomes. Stata 15.0 software was used for statistical analysis. Twenty-eight publications and 29 studies involving 508 animals were included in the meta-analysis. The results showed that BBR reduced disease activity index (DAI) scores, alleviated UC-induced colon length (CL) loss, prevented weight loss, and reduced histological colitis score (HCS). Mechanistically, BBR was found to reduce myeloperoxidase (MPO) activity and malondialdehyde (MDA) levels, reduce levels of pro-inflammatory factors interleukin-1β (IL-1β), interleukin 6 (IL-6), tumor necrosis factor α (TNF-α), interferon-γ (IFN-γ) and mRNA expression of interleukin 17, increase levels of anti-inflammatory factor interleukin 10 (IL-10), and to increase levels of tight junction protein zonula occludens-1(ZO-1) and occludin, which may involve antioxidant, anti-apoptotic, neuromodulation, anti-fibrotic, anti-inflammatory, barrier protection, and flora regulation aspects. However, additional attention should be paid to these outcomes due to the heterogeneity and methodological quality of the studies.